Ð¡Ñ‚Ð¸Ð¼ÑƒÐ»Ð¸Ñ€ÑƒÑŽÑ‰ÐµÐµ Ð´ÐµÐ¹ÑÑ‚Ð²Ð¸Ðµ Ð¼Ð°Ð»Ñ‹Ñ… Ð´Ð¾Ð· Ð¾Ð·Ð¾Ð½Ð° Ð½Ð° Ñ€Ð¾ÑÑ‚ Ð¼Ð¸ÐºÑ€Ð¾Ð¾Ñ€Ð³Ð°Ð½Ð¸Ð·Ð¼Ð¾Ð² - Belykh, I. A.; Zinchenko, V. D.; Vysekantsev, I. P. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2004)
Ozone in dosed amount was added to growth medium of Esherichia coli bacteria or Candida albicans yeast-like fungi and the kinetics of microorganism growth depending on its amount was under observation. With the ozone dose of 0.3-0.5 mg/l in growth medium there was found the growth stimulation of microorganisms, with higher doses the growth suppression was found. If Candida albicans fungi are subjected to freezing down to â€“196Â°C and then to thawing, then with adding ozone to growth medium before freezing more intensive fungi growth after thawing is noted.